Classical commentaries : explorations in a scholarly genre - Kraus, Christina A.; Kraus, Christina A.; Stray, Christopher; Stray, Christopher (Oxford University Press, 2016)
This rich collection of essays by an international group of authors explores a wide range of commentaries on ancient Latin and Greek texts. It pays particular attention to individual commentaries, national traditions of commentary, the part played by commentaries in the reception of classical texts, and the role of printing and publishing